Optimization of Well Placement Based on Reservoir Fluid Contact - Irawan, Sonny (Penerbitan Universitas Trisakti, 2024)
The development of oil fields was often troubled with the predicament of figuring the optimum well location, been it vertical or horizontal wells. The process of hydrocarbon resources extraction from a reservoir which was economically effective is required for producers and injectors to drilled and positioned at an optimal location. One of the contributing factors of decided an optimized location of well is reservoir fluid contact, gas-oil contact (GOC) and oil-watered contact (OWC). Reservoir overlying a strong aquifer typically had high watered cut thus impairing oil production rate also, leads to water coning. The optimized location of well could have affected by water coning mechanism in oil-water and gas-water system differently due to the density difference of the hydrocarbon. Water coning due to increased water cut in the OWC region is the most common phenomena therefore, the purpose of this studied is to observed water cut increment along production period. Besides, monitoring downhole well constraint in water cut and production rate estimation could also be done in ordered to estimate optimal location or placement of horizontal well with respect to GOC and OWC. Vertical and horizontal well placement is simulated with varying downhole constraints to ensured efficient production rate of hydrocarbon. Therefore, estimation of water cut and breakthrough timed is conducted after increased in water cut thus, oil production rate and oil recovery factor against water cut increment could be generated to illustrate which well showed highest productivity and efficiency.